AL-QURâ€™AN SEBAGAI MEDIUM PENYEMBUHAN DALAM TRADISI â€œBEJAMPIâ€ DI LOMBOK (Kajian Living Qurâ€™an) - Hasan, Muhammad Zainul (UIN Mataram, 2020)
â€œOn the cultural plane, Muslim societies (Islamic societies) have active interactions with the Qur'an. Interaction in the form of making the Qur'an as a medium in living life. Interaction with al-Qur'an is built from reason (iqtiqadiyah). This article analyzes the tradition of bejampi in Lombok society with a framework of living Qur'an studies, phenomenological approaches and exploratory analysis. The bejampi tradition in the Lombok community has strong historical roots and a strong religiosity. Pejampi are those who have followed the Koran of Islamic learning to learn the nature of the essence and makrifat. The bejampi tradition uses verses of the Qur'an as a medical medium such as: An-Nass, Fatihah, al-Kahf, al-Fath and al-Insyirah. This verse is used to cure self-illness / distress / illness, medical illness and non-medical illness. Living Qur'an in the tradition of bejampi Lombok people shows that the al-Qur'an has magical and medical power.â€